Accelerating Certification of Oil Palm Smallholders through Institutionalization of Various Incentives - Wibowo, Lukas Rumboko; Erdi, Erdi; Hutabarat, Sakti; Nurfatriani, Fitri Nur; Utomo, Marcellinus; Nawireja , Iman Kasiman; Pramudya, Eusebius Pantja; Kurniasari , Dewi Ratna; Cahyono , Eko; Kurniadi, Rahman; Santosa , Andri; Fuad , Zainal; Satwiko , Aria Atyanto (Forest and Society, 2023)
Sustainable palm oil certification has become a global demand, particularly in the market. However, the implementation of both Roundtable of Sustainable Palm Oli (RSPO) and Indonesian Sustainable Palm Oil (ISPO) certification schemes is relatively slow. This study aims to analyze to what extent incentives can accelerate sustainable palm oil certification, from what sources those incentives can be arranged, and types of incentives are appropriate for palm oil smallholders. The research uses quantitative and qualitative methods based on literature reviews, in-depth interviews with key stakeholders, and a survey of 455 farmers in two Indonesian provinces (Riau and West Kalimantan). Based on quantitative analysis, the reasons behind more progressive certification achievements in Riau remain unrevealed while in West Kalimantan, Fresh Fruit Bunches (FFB) price, easiness to obtaining loans with low interest, and easiness of selling FFB have a significant influence on accelerating certification. Using a qualitative approach, smallholders show their expectation of having incentives. In Riau, incentives expected are higher FFB prices and a simpler procedure to get the Environmental Management Statement (SPPL) document. In West Kalimantan, higher FFB prices and availability of low interest loans are expected to become incentives. These incentives can be mobilized from intergovernmental fiscal transfer mechanisms such as revenue-sharing mechanisms, export levies, and environmental funds. Smallholders also expect clarity of incentives generated from ISPO certification, particularly in price and market access, which requires the government’s initiative to develop synergy with various stakeholders. To be practical, incentives were not only for smallholders but also for the government officials at the province, district, and village levels, as the position of the local government is very important in preparing, encouraging, and mobilizing farmers, as well as in strengthening institutions for improving palm oil governance. In the implementation of RSPO certification, the collaboration between the Indonesian government (through the Ministry of Cooperatives and Small and Medium Enterprises) and the RSPO becomes clear evidence of central government support. At the sub-national level, the Riau and West Kalimantan Provinces have developed the Regional Action Plans (RAD) for sustainable palm oil as a policy commitment to accelerate both RSPO and ISPO certification.